(untitled) (Educação e Pesquisa, 2020)
The purpose of this research is to identify the development of academic competences in college teaching from the professors’ perspective, with the contribution of the theory of social representations. To collect information, the instrument called the Free Word Association Test, possessing a projective ethos, was applied to 154 college professors from three private institutions in Distrito Federal (BR). The prototypical analysis was a product of the software IRaMuteQ, which analyzed the words mentioned by professors when the inducing expression develop competence’s academic is... was used. The central nucleus was composed of the following words: training, competence, reflection, fundamental, responsibility and development. On the other hand, in the contrasting elements the terms scientific, ethical, autonomy, focus, ability and planning emerged. These data point to the promotion of the learning process based on the active and interactive conception of the process, with the student as the protagonist. The data show the construction of knowledge, appropriation of different knowledges, mobilization of doing and the theoretical-practical articulation within a humanizing, ethical and aesthetic perspective. Still, it can be recognized that the development of competences is not restricted to the operative dimension, but involves the technological, methodological, didactic, relational and it is also linked to the sphere of work, in addition to the social, cultural and professional aspects being inseparable. It is a professional teaching project that assumes a vision of society in which the ethical process and the political, methodological, operational, technical dimension interpenetrate and are transversalized by the humanist perspective, so that commitment, responsibility and reflection are constant demands transformations in the world of work and social problems.